ASME 2009 Summer Bioengineering Conference, Parts a and B 2009
DOI: 10.1115/sbc2009-206815
|View full text |Cite
|
Sign up to set email alerts
|

Load Transfer Along the Bone-Dental Implant Interface

Abstract: Endosseous dental implants are used as prosthetic treatment alternatives for treating partial edentulism [1]. Excellent long term results and high success rates have been achieved using dental implants during the past decades. Further improvements in implant protocols will include immediate loading, patient specific implants, applications for patients with extreme bone loss and extreme biting habits such as bruxism. The implant designs available in the market vary in size, shape, materials and surface characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similar values have been reported in the literature[3,8,10,20] …”
supporting
confidence: 91%
“…Similar values have been reported in the literature[3,8,10,20] …”
supporting
confidence: 91%
“…Several studies have demonstrated that by changing the implant surface, the rate of osseointegration and the percentage of bone-to-implant contact (BIC) can be significantly improved [11,12,13,14]. Furthermore, is has been highlighted that the most relevant implant surface properties impacting the adhesion and the survival of cells are chemical composition, surface energy, wettability (hydrophobicity/ hydrophilicity), roughness, topography and surface morphology.…”
Section: Implant Surfacementioning
confidence: 99%
“…20,21 In the case of dental implants, the stress concentration is usually found at the portions interfacing with the cortical bone. 22,23 Like classical design optimization, the mathematical algorithm of TO is based on design variables, objective function, and constraints. 20 This method uses FEA to iteratively evaluate the design performance, allowing the removal of redundant material while keeping the structural stability and functional characteristics intact.…”
Section: Introductionmentioning
confidence: 99%